2000
DOI: 10.1021/ma9908189
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation and Rheological Properties of Polyurethane Melts. 3. Effect of Block Incompatibility on the Viscoelastic Properties

Abstract: The accompanying paper described the structural characterization of polyurethane multiblock copolymers that varied block incompatibility at fixed block length and composition. Their linear viscoelastic properties are presented in this paper. Dynamic mechanical experiments in temperature sweep mode confirmed that the materials ranged from almost homogeneous to highly microphaseseparated. Dynamic mechanical frequency sweep experiments showed a Rouse-like frequency response in all materials at high temperatures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 23 publications
3
42
1
1
Order By: Relevance
“…In this system the incompatibility is found to be the maximum. Our results are very consistent with experimental studies, which show that the thermodynamic immiscibility between hard and soft segments influence the formation of the microphase-separated microstructure of the segmented copolymers from nearly mixed to strongly microphase separated ones [68]. These results also are supported by the FTIR spectroscopic studies, which showed that kinetics and extent of microphase separation is directly related with the structure of the HS [69,70].…”
Section: Calculation Of Flory-huggins Interaction Parameterssupporting
confidence: 92%
“…In this system the incompatibility is found to be the maximum. Our results are very consistent with experimental studies, which show that the thermodynamic immiscibility between hard and soft segments influence the formation of the microphase-separated microstructure of the segmented copolymers from nearly mixed to strongly microphase separated ones [68]. These results also are supported by the FTIR spectroscopic studies, which showed that kinetics and extent of microphase separation is directly related with the structure of the HS [69,70].…”
Section: Calculation Of Flory-huggins Interaction Parameterssupporting
confidence: 92%
“…Compositions of the materials were found using quantitative 13 C nuclear magnetic resonance (NMR) spectroscopy on a 240 I725-0 48 0 I725-12 725 40000 47 12 I725-25 46 25 I725-40 45 40 I1000-0 47 0 I1000-13 1000 36000 46 13 I1000-32 45 32 I1000-40 45 40 I2000-0 57 0 I2000-14 2000 29000 55 14 I2000-29 54 29 IPDI/DMP 36700 0 a Estimated error (2%. b Estimated error (3%.…”
Section: Methodsmentioning
confidence: 99%
“…From the Fig. 13(a), it was observed that microphase separation is weak in high frequency dynamic mechanical experiments [3,57]. Fig.…”
Section: Dynamic Mechanical Analysesmentioning
confidence: 97%